Israel and Palestine out of the Ashes: The Search for Jewish Identity in the Twenty-First Century by Marc H. Ellis (London and Sterling, Virginia: Pluto Press, 2002. 198 pages.) (American Journal of Islam and Society, 2004)
During the more than 37-year brutal Israeli occupation of the West Bankand Gaza, the numbers of North American Jews voicing their oppositionin public have been dispiritingly small. Since the outbreak of the secondIntifada in September 2000, however, Jewish anti-occupation activistshave become a visible political presence in Jewish politics in the UnitedStates and Canada. Such groups as Brit Zedek V’Shalom, the TikkunCommunity, and Junity (Jewish Unity for a Just Peace) have spawneddozens of regional chapters across North America. Local groups such asNot In My Name (Chicago), Jewish Voices against the Occupation(Seattle), and Jews for Global Justice (Portland, Oregon) have sprung upspontaneously in almost every major North American city. Numerous adhoc responses have emerged as well. For example, an “Open Letter fromAmerican Jews,” proclaiming opposition to Israeli government policies inthe Occupied Territories and bearing 4,000 signatures, has appeared as afull-page advertisement in The New York Times as well as in a dozen moreAmerican and British newspapers.While very few of these groups would identify themselves as religiouslyobservant, almost all have invoked a Jewish ethical tradition ofsocial justice, derived from Jewish texts and rabbinical tradition, to maketheir political point. In his most recent book, Israel and Palestine out of theAshes, Jewish theologian Marc Ellis posits a more deeply consequentialconnection between Jewish history, Jewish ethics, and the occupation.According to Ellis, Director of the Center for American and Jewish Studiesat Baylor University (Waco, Texas), Israel’s displacement and dispossessionof the Palestinian people constitutes such a fundamental transgressionof Jewish ethics and morality that it threatens to render Judaism, a religious ...